THE PLAIN LANGUAGE MOVEMENT AND MODERN LEGAL DRAFTING - SOBOTA, Anna (Comparative Legilinguistics, 2016)
This paper aims to answer the question whether modern legal drafting is implementing the revolutionary changes argued for by the plain language movement and whether legal texts are made more user-friendly, particularly to their non-professional recipients. The paper discusses the main characteristics of modern legal drafting against the background of research conducted in 2011 and 2012 based on a broad selection of American consumer contracts. The interest centres on the successes rate of the plain language campaigners as well as the threats to their pursuit of plain legal drafting.